Senam Hipertensi Bagi Lanjut Usia (LANSIA) Di Posyandu Cekke Kabupaten Enrekang - Dunggio, Abdul Rivai Saleh; Hardin, Hardin; Pratiwi, Cici; Mesa, Nofita Dewi Kok; Hoda, Ferdinandus Suban (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
Hypertension exercise is an exercise that aims to increase blood flow and oxygen supply to active muscles and skeleton, especially the heart muscle, so that it can reduce blood pressure. The aim of this community service (PkM) is to increase the understanding of elderly people about hypertension elderly exercise and to determine the effect of elderly hypertension exercise on the blood pressure of elderly people with hypertension in the Posyandu Cekke work area, Enrekang Regency. The method used to achieve the target of this activity is by approaching, lecturing and jointly doing exercises for the elderly with hypertension. The final outcome of this PkM activity is that it can increase the client's knowledge about exercise for the elderly with hypertension and can control complications of hypertension, namely stroke due to hypertension in old age. The method for implementing community service (PkM) is by using counseling which aims to gain knowledge about the importance of exercise for the elderly. It is hoped that after getting the theory about the importance of exercise for the elderly, they will be able to increase their knowledge and be willing to do exercise either at the Posyandu for the Elderly or at home. The result of this community service (PkM) is an increase in the elderly's knowledge about the importance of posyandu, which can be seen from the results of the pre-test and post-test, namely an increase of 32%. Increasing the activeness of elderly people in posyandu and motivation for elderly exercisers to always take part in elderly exercise seriously.